Omega-3-fatty acids from algae for health benefits. (2022) - Priyadarsini, Meenakshi; Raichel Nivetha, X.; Mathimani, Thangavel; Anto, Susaimanickam; Hareesh Krishnan, H.; Glivin, Godwin; Premalatha, M.; Mariappan, V.; Sekhar, Joseph
Abstract: Algal biotechnology grew progressively into a widespread industry with escalating statistics of entrepreneurial inventions endeavoring the utilization of its biochemical assortment for a broad range of applications in the recent past. They find their application in various industries such as the pharma and nutraceutical industries that use high-value biologically active ingredients such as omega-3 fatty acids, carotenoids, and other significant products. The algal growth metabolism is attractive to the eyes of researchers because of their potential to undergo photosynthesis alike the plants and unlike other microorganisms. They have a high adaptive capability, which helps them endure extreme environments such as temperature, salinity, pH, and photoperiod. Since they are photosynthetic organisms, they can harness their energy easily from CO2 and sunlight. In a biorefinery concept, omega-3 fatty acids extracted from microalgae are extensively applied in the field of nutrition and thus paving the way for the development of a cost-effective microalgal bio-refinery. Furthermore, the production of a high-value product, such as omega-3 from microalgae, will help promote the establishment of the microalgal industry for entrepreneurs. This article reviews the importance of omega 3 fatty acids, challenges in microalgal ω-3 fatty acids extraction, Lipid extraction methods used and their significance, and more feasible, yet, lucrative techniques for extraction in the current scenario.